The pocket Thich Nhat Hanh - Hanh, Thich Nhat.; McLeod, Melvin (Colorado : Shambhala, 2017)
Since Thich Nhat Hanh$1 (Bs exile from his native Vietnam in 1966, this Zen Buddhist monk has gone on to become one of the most influential and beloved spiritual masters of our age. The seeming simplicity of his words belies the power of this teaching to touch the heart and mind and to inspire spiritual practice. These selections, taken from his many published works, together make up a concise introduction to all his major themes and distill his teachings on the transformation of individuals, relationships, and society.s
Keywords: Religious life -- Buddhism; Zen Buddhism